Students’ Perceptions of Information Literacy at two South African Universities - Moyo, Mathew; Okemwa, Ezra Ondari (Library Philosophy and Practice (e-journal), 2022)
Information literacy, the ability to find and use information ethically, has been on the agenda of academic librarians for a very long time now. The driving force behind the information literacy agenda is the over-abundance of information, particularly online, as a result of rapid changes and developments in technology (Tosuncuoglu & Küçükler, 2019). There is a general shift in the publications industry, with increasingly more information being published online and this has resulted in an influx of information available to users in general and to students in particular. The current COVID-19 pandemic has added more impetus to the critical value of information literacy as fake news infodemic has risen to levels demanding high critical thinking skills (Durodolu & Ibenne, 2020; Guo & Huang, 2021). Seemingly, academic integrity has once again become a major issue on campus as students became overwhelmed by the sudden transition from contact teaching and learning, to the online modality which has enabled the continuation of the University’s core business under the Coronavirus environment. From a practical experience, the authors have experienced a surge in instances of plagiarism resulting in punitive policies being invoked on offenders in order to help reduce the cases. Librarians, as custodians and facilitators of access to information of all kinds, have a huge role to play in ensuring that students acquire the necessary skills in order to properly handle information. The South African University System is usually classified into historically advantaged and historically disadvantaged. Students joining the historically advantaged institutions usually originate from the rich urban families while those attending the formerly disadvantaged institutions come from mostly rural based schools without access or with limited access to libraries and technology of all kinds. If our primary and secondary education system was adequately paying attention to learners’ information handling skills including the entire digital skills spectrum, information literacy would not be a major concern at the higher education level. This background information which include the renewed need for information literacy education during the ongoing COVID-19 pandemic, motivated the researchers to rework and share this outcome from a study conducted some few years back.